Contrafaction in Lithuanian book publishing during the first half of the XIX century - Aušra Navickienė (Knygotyra)
Contrafactions or the publications with falsified imprint are not characteristic for the first half of the 19th century in Lithuania. Only one possible case of a contrafaction from the period 1795-1864 is mentioned in the first volume of Lithuanian retrospective bibliography of Lithuanian books (Lietuvos TSR bibliografija. Serija A Knygos lietuvių kalba). These are the repeated editions of the publication About Teetotalers' Brotherhood (Apej brostwą blaiwistes) by Bishop Motiejus Valančius. They appeared in 1860 and 1861 and could have been printed not in Klaipėda as the title page indicates, but in the Vilnius printing house of J. Zawadzkis. There is no one final opinion about this fact, and the article returns to the publishing history of the book by Valančius because it is important for establishing the beginning of the book relations between Great Lithuania and Lithuania Minor. Usually, it is linked to the publishing of the above-mentioned book in Klaipėda.